A novel method for soft tissue retraction during periapical surgery using 3D technology: a case report. (12th October 2016) - Patel, S.; Aldowaisan, A.; Dawood, A.
Abstract: Aim: This case report describes a new approach to isolation and soft tissue retraction during endodontic surgery using cone‐beam computed tomography (CBCT), computer‐aided design (CAD) and three‐dimensional (3D) printing. Summary: A 53‐year‐old patient presented for endodontic treatment of her maxillary left central incisor. It was decided to treat this tooth with a microsurgical approach. The data from the diagnostic CBCT scan were also used to make a physical model of the operative site, and CAD software was used to design a soft tissue retractor to be used during the patient's surgery. A custom retractor was then fabricated using a 3D printer. The custom‐made retractor enhanced visualization and soft tissue handling during the patient's surgery. The patient was asymptomatic at a 1‐year review. No abnormalities were detected during her clinical examination, and radiographic examination revealed complete healing of the surgical site. Key learning points: The significance of proper soft tissue retraction in periapical microsurgery is underemphasized. Geometric data from CBCT scans may be harvested for a variety of uses, adding value to the examination. 3D printing is a promising technology that may potentially have many uses in endodontic surgery.